Synthesis of Mg/Al Hydrotalcite by Using Low Supersaturated Precipitation Method with Variation of Mole Ratio - Christanty Wahyu Septyaningrum; Sri Handayani; Cahyorini Kusumawardani; Kun Sri Budiasih (EKSAKTA: Journal of Sciences and Data Analysis, 2014)
This research aims to synthesize Mg/Al hydrotalcite with mole ratio variations of Mg/Al precursor through low supersaturated precipitation method. Mg/Al hydrotalcite was synthesized with Mg/Al mole ratio variation of 1:1, 2:1, 3:1, and 4:1. Mg/Al hydrotalcite was synthesized using NaOH and Na2CO3 base solutions. The mixture of precursor was stirred for 2 hours then treated by hydrothermal at 100 °C for 4 hours. Results of the synthesis Mg/Al hydrotalcite with mole ratio variations is a white powder. The formation of the structure of Mg/Al hydrotalcite showed by certain peaks in the FTIR spectra and XRD diffractogram.The results of data analysisshowed that variation of mole ratio Mg/Alcauses a shift of peak in the XRD diffractogram shifted towards the left along with a comparative increase in mole ratio Mg/Al, but the main functional groups on the compound Mg/Al hydrotalcite increasingly formed with better.